Variations in coronary artery anatomy: Normal versus abnormal - Trivellato, M. (1980)
We offer a comprehensive classification of coronary artery anomalies, together with angiographic examples of each entity. Minimal requirements for normality include the following criteria: (1) the dual aortic origin is from right and left coronary ostia; (2) the course of the right coronary artery follows the right atrioventricular groove; (3) the course of the left coronary artery follows the left atrioventricular groove and anterior interventricular groove; (4) the posterior descending branch originates from either the right or left coronary artery; (5) the major coronary branches flow epicardially; and (6) the coronary arteries terminate at the myocardial capillary level. This conception of “normal” coronary arteries has determined the classification of abnormalities presented here. Early and correct diagnosis of anomalies that may compromise the myocardial blood supply is stressed, and possible surgical solutions are offered. Selective coronary angiography is the technique of choice for precise visualization of the coronary artery system.